THE RELATIONSHIP BETWEEN ARM MUSCLE STRENGTH AND LEG MUSCLE STRENGTH TOWARDS 50-METER FREESTYLE SWIMMING SPEED - Johanna Matitaputty (EDU SCIENCES JOURNAL, 2020)
This study aims to determine the relationship between arm muscle strength and leg muscle strength towards 50-meter freestyle swimming speed of Physical Education Students Major, at FKIP Unpatti Ambon. Based on the results of the analysis of leg muscle strength variables with a swimming speed of 50 meters crawl stroke of male students in Health and Sport Study Program of FKIP Unpatti Ambon Fcount = 3,61 > Ftable (dk = 28 and Î± = 0,05) = 1,70 at the level Î± = 0.05 and means the null hypothesis (H0) is rejected. Based on the analysis of the variable arm muscle strength with a swimming speed of 50 meters crawl stroke of male students in Health and Sport Study Program of FKIP Unpatti Ambon, the results obtained Fcount = 3,47 > Ftable (dk = 28 and Î± = 0,05) = 1.70 at the level Î± = 0,05 and means the null hypothesis (H0) is rejected. Based on the analysis of the relationship between leg muscle strength, arm muscle strength, and swimming speed 50 meters crawl stroke of male students in Health and Sport Study Program of FKIP Unpatti Ambon, the result obtained Fcount = 14,99 > Ftable (dk = 28 and Î± = 0,05) = 1,70 at the level Î± = 0,05 and means the null hypothesis (H0) is rejected. Thus, the stronger the leg muscles and arm muscles, the better the crawl stroke speed of students of the Health and Sport Study Program of FKIP Unpatti Ambon